2020
DOI: 10.1017/wsc.2020.7
|View full text |Cite
|
Sign up to set email alerts
|

Seed production and retention at maturity of blackgrass (Alopecurus myosuroides) and silky windgrass (Apera spica-venti) at wheat harvest

Abstract: Blackgrass (Alopecurus myosuroides Huds.) and silky windgrass [Apera spica-venti (L.) P. Beauv.] are becoming a significant problem in Europe. Due to the development of herbicide-resistant biotypes and unwanted side effects of herbicides, there is a need for new integrated weed management strategies to control weeds. Therefore, reducing weed infestations by targeting seed production during crop harvest should be considered. In 2017 and 2018, we estimated the fraction of the total seed production of A. myosuroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…The pattern of seed shedding between V. myuros and L. multiflorum was inconsistent across the years probably because of different growing conditions between the 2 years ( Figure 1). Similar to our results, Bitarafan and Andreasen [41] reported earlier seed shedding in A. myosuroides than A. spica-venti over two growing seasons, and variation in the timing of seed shedding due to different climatic conditions was observed between the years. The percentages of seeds retained on the plants of A. spica-venti and A. myosuroides were 35% and 34%, respectively, at winter wheat harvest in Denmark [41].…”
Section: Seed Shedding and Seed Productionsupporting
confidence: 91%
“…The pattern of seed shedding between V. myuros and L. multiflorum was inconsistent across the years probably because of different growing conditions between the 2 years ( Figure 1). Similar to our results, Bitarafan and Andreasen [41] reported earlier seed shedding in A. myosuroides than A. spica-venti over two growing seasons, and variation in the timing of seed shedding due to different climatic conditions was observed between the years. The percentages of seeds retained on the plants of A. spica-venti and A. myosuroides were 35% and 34%, respectively, at winter wheat harvest in Denmark [41].…”
Section: Seed Shedding and Seed Productionsupporting
confidence: 91%
“…The successful implementation of weed seed harvest in Australia can be attributed to the fact that a large fraction of L. rigidum seeds is retained at crop maturity [84]. Visual observations indicate that V. myuros sheds the majority of its seeds several weeks before winter wheat maturity, as was recently observed for A. spica-venti and A. myosuroides [85]. Thus, the weed seed harvest method may not be as effective as for L. rigidum, but it may contribute to the long-term control of V. myuros and serve as a last resort in fields where other control measures have failed.…”
Section: Weed Seed Harvestmentioning
confidence: 67%
“…Thereby, the seeds are not incorporated into the soil seed bank, creating new weed problems in the coming season. However, many weed species shatter a smaller or larger proportion of their seeds before harvest [38,39]; therefore, the effect strongly depends on the weed composition in the field. Walsh and Powels [40] found that some of the most important weed species in Australia-L. rigidum, Raphanus raphanistrum L., Bromus spp., and Avena fatua L.-retained 85%, 99%, 77%, and 84% of their seeds above a 15 cm harvest cutting height at wheat (Triticum aestivum L.) maturity.…”
Section: Discussionmentioning
confidence: 99%